Quiescence near the X-point of MAST measured by high speed visible imaging. (25th September 2017) - Walkden, N.R.; Harrison, J.; Silburn, S.A.; Farley, T.; Henderson, S.S.; Kirk, A.; Militello, F.; Thornton, A.
Abstract: Using high speed imaging of the divertor volume, the region close to the X-point in MAST is shown to be quiescent. This is confirmed by three different analysis techniques and the quiescent X-point region (QXR) spans from the separatrix to the ψ N = 1.02 flux surface. Local reductions to the atomic density and effects associated with the camera viewing geometry are ruled out as causes of the QXR, leaving quiescence in the local plasma conditions as being the most likely cause. The QXR is found to be ubiquitous across a significant operational space in MAST including L-mode and H-mode discharges across maximal ranges of 9.8 × 10 19 m − 2 in line integrated density, 0.36 MA in plasma current, 0.11 T in toroidal magnetic field and 3.2 MW in NBI power. When mapped to the divertor target the QXR occupies approximately an e-folding length of the heat-flux profile, containing ̃60% of the total heat flux to the target, and also shows a tendency towards higher frequency shorter lived fluctuations in the ion-saturation current. This is consistent with short-lived divertor localised filamentary structures observed further down the outer divertor leg in the camera images, and suggests a complex multi-region picture of filamentary transport in the divertor.